PrhN, a putative marR family transcriptional regulator, is involved in positive regulation of type III secretion system and full virulence of Ralstonia solanacearum - Zhang, Yong; Luo, Feng; Wu, Dousheng; Hikichi, Yasufumi; Kiba, Akinori; Igarashi, Yasuo; Ding, Wei; Ohnishi, Kouhei (Frontiers in Microbiology, 2015)
The MarR-family of transcriptional regulators are involved in various cellular processes, including resistance to multiple antibiotics and other toxic chemicals, adaptation to different environments and pathogenesis in many plant and animal pathogens. Here, we reported a new MarR regulator PrhN, which was involved in the pathogenesis of Ralstonia solanacearum. prhN mutant exhibited significantly reduced virulence and stem colonization compared to that of wild type in tomato plants. prhN mutant caused identical hypersensitive response (HR) on resistant plants to the wild type. Deletion of prhN gene substantially reduced the expression of type III secretion system (T3SS) in vitro and in planta (mainly in tomato plants), which is essential for pathogenicity of R. solanacearum, and the complemented PrhN could restore its virulence and T3SS expression to that of wild type. T3SS is directly controlled by AraC-type transcriptional regulator HrpB, and the transcription of hrpB is activated by HrpG and PrhG. HrpG and PrhG are homologues but are regulated by the PhcA positively and negatively respectively. Deletion of prhN gene also abolished the expression of hrpB and prhG, but didn't change the expression of hrpG and phcA. Together, these results indicated that PrhN positively regulates T3SS expression through PrhG and HrpB. PrhN and PhcA should regulate prhG expression in a parallel way. This is the first report on the pathogenesis of MarR regulator in R. solanacearum, and this new finding will improve our understanding on the various biological functions of MarR regulator and the complex regulatory network on hrp regulon in R. solanacearum.